2020
DOI: 10.1126/science.abd0609
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of nucleosome-dependent cGAS inhibition

Abstract: Cyclic GMP-AMP synthase (cGAS) recognizes cytosolic foreign or damaged DNA to activate the innate immune response to infection, inflammatory diseases, and cancer. In contrast, cGAS reactivity against self-DNA in the nucleus is suppressed by chromatin tethering. We report a 3.3-angstrom-resolution cryo-electron microscopy structure of cGAS in complex with the nucleosome core particle. The structure reveals that cGAS employs two conserved arginines to anchor to the nucleosome acidic patch. The nucleosome binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(130 citation statements)
references
References 45 publications
6
124
0
Order By: Relevance
“…In parallel with this study, five other groups also reported on the cryo-EM structures of human and mouse cGAS-nucleosome complexes. [11][12][13][14][15] We note that the 2:2 and higher-order assemblies mediated by cGAS site C are observed in all three human cGAS-NCP structures 9,12,15 but not in their mouse counterparts. 11,13,14 Consistent with this distinction, site C has been shown to be an evolutionarily strengthened DNA-binding interface when proceeding from mouse to humans.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…In parallel with this study, five other groups also reported on the cryo-EM structures of human and mouse cGAS-nucleosome complexes. [11][12][13][14][15] We note that the 2:2 and higher-order assemblies mediated by cGAS site C are observed in all three human cGAS-NCP structures 9,12,15 but not in their mouse counterparts. 11,13,14 Consistent with this distinction, site C has been shown to be an evolutionarily strengthened DNA-binding interface when proceeding from mouse to humans.…”
mentioning
confidence: 65%
“…The studies discussed here 9,[11][12][13][14][15] provide compelling evidence of cGAS sequestration and inhibition by the nucleosome, with such nuclear tethering trapping cGAS in an inactive conformation. Fig.…”
mentioning
confidence: 73%
“…Another structure by Boyer et al reported the structure of cGAS bound to a single nucleosome. This binding sterically abrogates cGAS oligomerization required to yield functionally active 2:2 cGAS-dsDNA complex (112). These recent findings have provided important information that how cGAS is maintained in an inhibited state in the nucleus.…”
Section: Cgas-sting Pathwaymentioning
confidence: 88%
“…6A, Figure S3D). It was reported that cisplatin induced dsDNA fragments through accumulation of DNA damage and inhibiting DNA homologous complementary repair pathway 16 . We observed the signi cant increase of DNA damage marker γ-H2A.X in T24 and TCCSUP cell lines treated with cisplatin (Fig.…”
Section: Cisplatin Induced Dsdna May Function As An Important Role Inmentioning
confidence: 99%
“…For instance, translocation of cGAS from cytoplasm to cell membrane helps THP-1 and HeLa cells to recognize the exogenous virus DNA 37 . And nuclear translocation of cGAS can affect its functions by suppressing homologous recombination mediated repair 16 . But we found that cGAS was mainly located in nucleus in T24 and TCCSUP cell lines, and this subcellular distribution was not changed after cisplatin treatment.…”
mentioning
confidence: 99%